Utilization of Artificial Intelligence through Value Co-Creation in increasing MSME Sales based on Local product advantages - Fauzi, Maulidza Nur; Musarofah, Siti; Askhar, Bayu Malikhul; Septiana, Anggraeni Sovin Maria; Hidayatunnisa, Amelia (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) constitute a significant economic sector in Indonesia, accounting for 97% of the country's workforce and contributing 61.07% of the country's GDP (BPS, 2023). In Lamongan Regency, there are 120,235 MSMEs that contribute to 55.27% of GDP and 78.49% of the workforce. The objectives of this study are to comprehend the role that AI plays in value co-creation in MSMEs, to pinpoint and examine the ways in which AI supports value co-creation, and to create a thorough framework for examining the effects of AI on value co-creation in MSMEs. This study employs an explanatory research paradigm in conjunction with a quantitative technique. The sample studied was 120 respondents and quantitative data sampling using simple random sampling then processed using SEM PLS 3.0. The study's findings support the first hypothesis, which states that artificial intelligence improves sales performance. According to the second hypothesis, Value Co-creation can act as a mediator between artificial intelligence and sales performance. According to the third hypothesis, Value Co-Creation improves sales performance. The fourth hypothesis then demonstrates that the relationship between Value Co-Creation and Sales Performance can be moderated by Product Excellence.